Como o 3˚ molar interfere na fragilidade do ângulo mandibular no momento de um trauma na região de corpo da mandíbula? : uma revisão integrativa da literatura e uma análise tridimensional por elementos finitos - Nogueira, Carlos Bruno Pinheiro (2024)
Experimental and observational studies have suggested that the mandibular angle (MA) may suffer fragility when the lower third molar (3M) is present. In mandibular trauma, energy dissipation may be influenced by the presence of these teeth. Therefore, this study aimed to identify the influence of 3M on the areas of energy concentration and dissipation in the AM region through computational simulations. A finite element study was carried out on a computed tomography scan of an adult individual, simulating trauma to the mandibular body in three experimental groups: bilateral absence of the 3Ms (group A), unilateral absence of the 3Mis on the same side of the trauma (group B), bilateral presence of the 3Ms (group C). Specific programs reproduced the mechanical and geometric characteristics of a mandible in real anatomical conditions. The pattern of energy dissipation after impact on the jaws presents notable variations between the groups analyzed, revealing distinct and, in some cases, similar movements. In terms of energy displacement, there was a similarity in the pattern between Groups A and B in relation to Group C. Important differences were also observed in the amplitude of stress in the MA region between the groups. In Groups A and B, the distal lingual and cervical regions of the second molar were Group A with a higher concentration of stress in the MA and Group C with no significant stress observed in the MA. Points of weakness were also observed in the area of ​​impact due to buccal and lingual trauma, as well as in the condyles in all groups. Therefore, we can conclude that the presence of 3M influences the way energy is distributed throughout the jaw and demonstrates an important relationship between the morphology of this bone and impact absorption, as well as the distribution of energy along the points of dental contact. to the side contralateral to the trauma.